Efeito relativo das mudanças climáticas e das mudanças do uso da terra na disponibilidade hídrica na bacia hidrográfica do Alto Paranapanema - Melo, Danielle Picão de (2024)
Climate change, together with changes in land use, are the main factors that contribute to changes in hydrological processes in river basins. Understanding the behavior of these processes in the face of these changes is of fundamental importance for planning and managing water resources, especially with regard to water availability. This study aims to evaluate how changes in climate variables (temperature and precipitation) interfere with water availability in the Jurumirim river basin (located in Alto Paranapanema) and discuss how future land use may affect or be affected by water availability for basin management purposes. For this purpose, the DinamicaEgo software was used for future land use scenarios (up to 2100) and the Soil and Water Assessment Tool (SWAT) model for hydrological modeling. The SWAT modeling included four climate models (Eta-BESM, Eta-Eta-CanESM2, Eta-HadGEM2-EM and Eta-Miroc5) and two emissions scenarios (RCP 4.5 and RCP 8.5), in the range from 1960 to 2099. The averages of the historical period (1960-1990) of the Eta-BESM model (RCP4.5) were used as a basis for comparison for the other models and periods (2010-2039 - near, 2040-2069 - medium and, 2070-2099 - distant). The land use transitions indicate increases in forestry and urbanization areas and reductions in pasture, native vegetation and agriculture by the end of the century. The reference model presents a historical monthly average of the rainy season between October and March and the dry season between April and September, with higher flows from December to May and lower flows from June to November. Future projections suggest an increase in temperature and an increase in precipitation in the driest months and a reduction in the rainy months, resulting in an annual loss of precipitation in most cases. Climate issues influence water availability more than changes in land use, where climate variables affect flow with reductions in the rainy season and increases in the dry season. In general, the RCP 8.5 scenarios tend to have greater losses and smaller gains compared to the RCP 4.5 scenarios, indicating lower water input into the hydrological system and longer dry periods. The Eta-BESM and Eta-HadGEM2-EM data, which best represent rainfall in the region, point to reductions in water availability, while Eta-Miroc5 shows an increase. Reductions in water availability highlight possible conflicts between multiple uses, which could negatively impact food and energy production and prices. It should be noted that the model has not yet been calibrated, but the results already allow us to understand the dynamics and patterns of rainfall and temperatures in the region.